Going Easy and Going After: Building Inspections and the Selective Allocation of Code Violations. (22nd May 2019) - Bartram, Robin
Abstract: Sociologists have demonstrated how public and private actors reproduce economic and racial inequality, by protecting the values of lucrative real estate, enforcing the tastes of elite and middle‐class populations, and unfavorably sorting low‐income and minority residents. Building inspections and code violations affect each of these processes. Yet, we know remarkably little about how decisions about building code violations are made. Drawing on fieldwork with building inspectors and statistical analysis of data on building violations in Chicago, I find that building inspectors allocate code violations in surprising ways: They go easy on low‐ and moderate‐income property owners and go after professional landlords and wealthy homeowners. I join others in urging sociologists to look beyond assumptions about the unified logic of the growth machine and fully unpack the relationship—in terms of potential and parameters—between frontline agents of the state and inequality.